Peningkatan Kesiapan Vaksinasi HPV Berbasis Video Interaktif di SDN Kebun Bunga 6 - Puteri, Nadya; Rahmah, Afiatun; Anwari, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2026)
Cervical cancer remains a major health problem for women, closely linked to Human Papillomavirus (HPV) infection. Preventive measures through HPV vaccination should be introduced from school age to increase vaccine readiness. If not accompanied by adequate knowledge, fear of the vaccine will become a barrier. Therefore, this activity aims to provide education and assess the knowledge and readiness of elementary school students, particularly at SDN Kebun Bunga 6, regarding HPV vaccination. The implementation method used in this community service activity consists of preparation and coordination, implementation, which begins with a pre-test, presentation of material through educational videos, evaluation through a post-test, and reporting. There were 10 questions in the pre-test and post-test tailored to the material presented. The results showed an increase in participants' understanding after the outreach activity. Given this improvement, it can be concluded that this community service activity was successful.